1997
DOI: 10.1002/srin.199700542
|View full text |Cite
|
Sign up to set email alerts
|

A study on the mechanism of reaction between refractory materials and aluminium deoxidised molten steel

Abstract: The conditions of formation of inclusions in steel during ladle refining in MgO‐C lined ladles have been investigated in laboratory experiments at 1873 K in MgO‐C crucibles with 50 g iron. From both the experimental results as well those of a thermodynamic study conducted in parallel, the following conclusions can be made about the reaction mechanism between the MgO‐C refractory and aluminium deoxidised molten steel: At steelmaking temperature an internal oxidation‐reduction occurs in the MgO‐C refractory. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 4 publications
(4 reference statements)
4
39
0
3
Order By: Relevance
“…21) This shows that even at a very low external pressure there are thermodynamic conditions under which the reaction of magnesium with molten steel occurs.…”
Section: Discussionmentioning
confidence: 99%
“…21) This shows that even at a very low external pressure there are thermodynamic conditions under which the reaction of magnesium with molten steel occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of a dense layer formation on the surface of the sample was achieved by the observation of the cross section of the sample after the oxidation test. It is interesting to note that the authors observed an increase in the oxidation rate when the oxygen potential pressure changes from 3.7ϫ10 2 Pa to 2.1ϫ10 4 Pa, as illustrated in Fig. 2.…”
Section: Introductionmentioning
confidence: 84%
“…[1][2][3][4] In MgO-C brick, carbon is also oxidized by magnesia according to the following reaction: The free energy changes for Eqs. (1)-(3) in the temperature range 298-2 000 K can be calculated as follows using standard reference tables 5) : DG 1 ϭϪ615 600ϩ1 118.23TϪRT ln P Mg ϪRT ln P CO .... (4) ...... (5) ......... (6) where p Mg is the partial pressure of Mg, p O2 is the partial pressure of O 2 and p CO is the partial pressure of CO.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great importance to investigate the reaction between ling refractory and the molten steel in order to control the generation of the exogenous inclusions from lining refractory. In order to clarify the reaction among steel, slag and lining refractory, theoretical and experimental work have been reported [4][5][6][7]. Brabie investigated the mechanism of the reaction between the MgObased ling refractory and Al killed steel and found that there was a thin oxide layer at the interface due to the reaction between the magnesium vapor and the dissolved aluminum [4].…”
Section: Introductionmentioning
confidence: 99%